2008
DOI: 10.1080/00140130701779197
|View full text |Cite
|
Sign up to set email alerts
|

The impact of operating heavy equipment vehicles on lower back disorders

Abstract: Literature reviews examining the relationship between heavy equipment vehicle (HEV) operation and the development of musculoskeletal disorders have generally been qualitative in nature and have not employed an evidence-based assessment procedure. This research determines the extent to which whole-body vibration/shock and working postures are associated with lower back and neck disorders among HEV operators, while accounting for individual (i.e. age, gender, prior history of back or neck disorders) and occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 48 publications
0
30
0
3
Order By: Relevance
“…In heavy equipment vehicle operators, LBP has been associated with steady-state whole-body vibration, as well as mechanical shocks induced by tough rides and high accelerations. 8 According to the Euro Back Unit Project, short-term LBP is back pain that affects the individual for less than 30 days in a year. 23 Methods used to treat acute LBP include medical, physiotherapeutic and/or chiropractic care.…”
Section: Low Back Painmentioning
confidence: 99%
See 1 more Smart Citation
“…In heavy equipment vehicle operators, LBP has been associated with steady-state whole-body vibration, as well as mechanical shocks induced by tough rides and high accelerations. 8 According to the Euro Back Unit Project, short-term LBP is back pain that affects the individual for less than 30 days in a year. 23 Methods used to treat acute LBP include medical, physiotherapeutic and/or chiropractic care.…”
Section: Low Back Painmentioning
confidence: 99%
“…7 Risk factors associated with the development of WMSDs include static work postures (trunk and neck twisting, stooping and deep sideways trunk bending), whole-body vibration, shock, physical work demands such as walking, pulling and lifting, climatic conditions, and psychosocial factors. 2,8,9 Obesity and decreased physical activity have also been associated with the development of WMSDs. 10,11 WMSDs can affect virtually all parts of the body, but the back, neck and shoulders and upper limbs account for more than 50% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have shown that heavy machinery operators are more likely to have low back problems than workers who are not exposed to whole body vibration [1,2]; this association has been further substantiated in a recent meta analysis which identified that operators exposed to driving heavy equipment vehicles are at more than twice the risk of developing lower back pain compared to individuals that are not exposed to driving heavy equipment vehicles [3]. Due to the high prevalence of heavy machinery in mechanized societies, between 4% and 7% of the work force in North America and Europe is exposed to potentially harmful levels of whole-body vibration [4,5].…”
Section: Introductionmentioning
confidence: 91%
“…Poor ergonomic cab design and operator's body posture, inadequate seat support and muscle fatigue have been described as co-factors in the development of musculoskeletal disorders of the spine in vehicle operators (Jorgensen et al, 2007;Pope et al, 1999;Waters et al, 2008). A review employing the Bradford-Hill criteria for assessing evidence of causation suggested that the evaluated data and studies support a causal link between back disorders and both driving occupations and whole-body vibration (Teschke et al, 1999).…”
Section: Introductionmentioning
confidence: 95%